Optimization of PSMA-I&T radiolabeling with 177Lu - Luiza Mascarenhas Balieiro; Maria das Dores Domingos; Luana Pereira da Silva; Joel Mendes dos Santos; Margareth Mie Nakamura Matsuda; Luis Alberto Pereira Dias; Elaine Bortoleti de Araújo (Brazilian Journal of Radiation Sciences)
Prostate cancer (PCa) is the second most common type of cancer in men and the fifth cause of mortality worldwide. Metastatic prostate cancer is associated with a poor prognosis and decreased life expectancy. Prostate-specific membrane antigen (PSMA) is a type II transmembrane glycoprotein that is anchored in the epithelial prostate cell membrane, overexpressed in prostate cancer, increased in metastatic castration-resistant prostate cancer (mCRPC) patients and with a consensus that its expression level is correlated to the malignancy of the disease. 177 Lu-PSMA-I&T stands out as a promissor radiopharmaceutical for therapy of prostate cancer and currently is being described based on this specifically bind to PSMA with the Glu-urea-Lys pharmacophoric group. This present work aimed to determine the most favorable conditions for labeling PSMA I&T with carried-added lutetium-177, evaluating the influence of molar ratio, pH, temperature and reaction time, to obtain the radiopharmaceutical with high radiochemical purity (%RP ≥95%), avoiding the final purification step. The percentage of radiochemical purity was evaluated by High Pressure Liquid Chromatography (HPLC) and Thin Layer Chromatography on silica gel 60 plate (TLC-SG). The results obtained with this work made it possible to define and standardize the best condition for PSMA I&T radiolabeling with carried-added 177Lu.